2013
DOI: 10.1002/grl.50122
|View full text |Cite
|
Sign up to set email alerts
|

Cirrus Cloud Seeding has Potential to Cool climate

Abstract: [1] Cirrus clouds, thin ice clouds in the upper troposphere, have a net warming effect on Earth's climate. Consequently, a reduction in cirrus cloud amount or optical thickness would cool the climate. Recent research indicates that by seeding cirrus clouds with particles that promote ice nucleation, their lifetimes and coverage could be reduced. We have tested this hypothesis in a global climate model with a state-of-the-art representation of cirrus clouds and find that cirrus cloud seeding has the potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(73 citation statements)
references
References 11 publications
2
68
3
Order By: Relevance
“…The large contribution from the clear-sky longwave fluxes in this case is consistent with what is found in WP10. The amplification in the longwave fluxes from the water vapor increase due to cirrus cloud seeding has also been noted in Storelvmo et al [2013]. (Table 3).…”
Section: The Effects Of Heterogeneous In In the Pd Simulationsmentioning
confidence: 61%
See 1 more Smart Citation
“…The large contribution from the clear-sky longwave fluxes in this case is consistent with what is found in WP10. The amplification in the longwave fluxes from the water vapor increase due to cirrus cloud seeding has also been noted in Storelvmo et al [2013]. (Table 3).…”
Section: The Effects Of Heterogeneous In In the Pd Simulationsmentioning
confidence: 61%
“…Global climate models have been used to study how heterogeneous IN and/or anthropogenic aerosols affect cirrus and climate [Hendricks et al, 2005;Lohmann et al, 2008;Liu et al, 2009;Penner et al, 2009;Wang and Penner, 2010;Hendricks et al, 2011;Gettelman et al, 2012;Liu et al, 2012a;Kuebbeler et al, 2014] and to further explore how cirrus seeding may cool climate [Mitchell and Finnegan, 2009;Storelvmo et al, 2013;Muri et al, 2014;Storelvmo and Herger, 2014]. Gettelman et al [2012] showed that black carbon aerosols have a small and not statistically significant aerosol indirect effects on cirrus when included as ice nuclei, for nucleation efficiencies within the range of laboratory measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Storelvmo et al (2013Storelvmo et al ( , 2014 have quantified the direct radiative effects produced by seeding uppertropospheric cirrus ice clouds with large IN. Although this is not directly related to our specific discussion on SG side effects, it can be considered as indirect evidence of the importance of correctly understanding the balance between the complex microphysical processes regulating the formation and growth of upper-tropospheric ice particles.…”
Section: Ice Formation Via Heterogeneous Freezingmentioning
confidence: 99%
“…Efficient ice nuclei (such as bismuth triiodide) seeding of cirrus cloud might artificially reduce their cover (Mitchell and Finnegan, 2009;Storelvmo et al, 2013).…”
Section: Isa-induced Cloud Albedo Increasementioning
confidence: 99%